Microcomputed tomography (laboratory and synchrotron) of intact archeological human second metacarpal bones and age at death. (19th October 2021) - Stock, Stuart R.; Mays, Simon; Turner‐Walker, Gordon; Soriano, Carmen
Abstract: Laboratory microcomputed tomography (microCT) and synchrotron microCT imaged intact human second metacarpal bones (mc2) from two UK archeological sites: Ancaster (3rd to 4th century CE) and Wharram Percy (11th to 14th century CE). Two female mc2 were studied from each of three age at death cohorts (young, 18–29 years; middle, 30–49 years; old ≥50 years) along with a modern control mc2. The present investigation is complementary with an X‐ray scattering study of the same mc2 where the authors found no age‐at‐death‐related changes in carbonated apatite lattice parameters and found collagen D‐period peaks in the small angle regime in a minority of the mc2. This led the present authors to ask whether microCT could assign mc2 to the age cohort estimated by dental wear and whether material between bioerosion porosity and apparently free of diagenetic changes correlated with presence of strong D period peaks. Lab‐microCT derived values of bone volume fraction BV/TV (bone volume BV divided by total volume TV) for distal and proximal metaphyses provided age estimates that agree with those of dental wear. Cortical microstructure corroborated the BV/TV determination. Synchrotron microCT revealed significant diagenesis in all of the Wharram Percy and two of the Ancaster mc2; the resulting microstructural changes were attributed to microbial attack. The Ancaster mc2 whose microstructure matched that of the modern mc2 had D‐period peaks with intensities matching the modern bone. MicroCT with different voxel sizes was shown, therefore, to be very useful in age determination and in the assessment of 3D diagenetic changes.